To solve the equation \(-2(4x + 8) + 2x = -5x + 10\), you can follow these steps in order:
-
Distribute the \(-2\) on the left side:
- This results in: \(-8x - 16 + 2x = -5x + 10\)
-
Combine like terms on the left side:
- Combine \(-8x\) and \(2x\) to get: \(-6x - 16 = -5x + 10\)
-
Isolate the variable:
- Add \(6x\) to both sides: \(-16 = x + 10\)
-
Solve for \(x\):
- Subtract \(10\) from both sides: \(-26 = x\)
Putting it all together, the correct steps are:
- Distribute \(-2\) to get \(-8x - 16 + 2x = -5x + 10\).
- Combine like terms to obtain \(-6x - 16 = -5x + 10\).
- Add \(6x\) to both sides, leading to \(-16 = x + 10\).
- Finally, subtract \(10\) to solve for \(x\), yielding \(x = -26\).